Disentangling genetic vs. environmental causes of sex determination in the common frog, Rana temporaria - Matsuba, Chikako (BioMed Central, 2008)
BACKGROUND: Understanding of sex ratio dynamics in a given species requires understanding its sex determination system, as well as access for reliable tools for sex identification at different life stages. As in the case of many other amphibians, the common frogs (Rana temporaria) do not have well differentiated sex chromosomes, and an identification of individuals' genetic sex may be complicated by sex reversals. Here, we report results of studies shedding light on the sex determination system and sex ratio variation in this species. RESULTS: A microsatellite locus RtSB03 was found to be sex-linked in four geographically disparate populations, suggesting male heterogamy in common frogs. However, in three other populations examined, no or little evidence for sex-linkage was detected suggesting either ongoing/recent recombination events, and/or frequent sex-reversals. Comparison of inheritance patterns of alleles in RtSB03 and phenotypic sex within sibships revealed a mixed evidence for sex-linkage: all individuals with male phenotype carried a male specific allele in one population, whereas results were more mixed in another population. CONCLUSION: These results make sense only if we assume that the RtSB03 locus is linked to male sex determination factor in some, but not in all common frog populations, and if phenotypic sex-reversals – for which there is earlier evidence from this species – are frequently occurring.